Peran Third Party Assurance, CSR dan Kinerja Keuangan: Financial Leverage sebagai Efek Moderasi - Rizka Yulia Shafira; Hersugondo Hersugondo (Politeknik Ganesha Medan, 2023)
The study aims to examine the mediating effect of third party assurance (TPA) and the moderating effect of financial leverage in corporate social responsibility (CSR) on the relationship between financial performance in the manufacturing industry in Indonesia. The research was conducted on manufacturing companies listed on the IDX in 2018-2020. The analytical method used is panel data regression analysis method and moderation regression model. The results of the study show that CSR has a positive effect on financial performance. TPA has a negative effect on financial performance and does not mediate the relationship between CSR and financial performance. Financial leverage is not significant with financial performance, but moderates the relationship between CSR and financial performance in pure moderation. Then, financial leverage is not significant with TPA, but it can moderate the relationship between CSR and TPA in pure moderation.